2020
DOI: 10.3390/brainsci10100758
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD20 Agents for Multiple Sclerosis: Spotlight on Ocrelizumab and Ofatumumab

Abstract: Until recently, in the pathogenesis of Multiple Sclerosis (MS), the contribution of B cells has been largely underestimated, and the disease was considered a T-cell-mediated disorder. However, newer evidence shows that B cells play a crucial role in the pathogenesis of MS via antigen-driven autoantibody responses and through the cross regulation of T-helper cells. As B cells express the surface molecule CD20 at all points of differentiation, it provides a specific target for monoclonal antibodies, and the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 61 publications
0
60
0
4
Order By: Relevance
“…These DMTs can also be classified broadly according to their pharmacological mechanisms of action. For example, dimethyl fumarate, teriflunomide, fingolimod, natalizumab, and the anti-CD20 agents ocrelizumab and ofatumumab [14] (the latter is newly approved for the management of RRMS in the USA) are continuously administered immunosuppressants. Interferons and glatiramer acetate are administered continuously and act via complex mechanisms that do not require a generalised suppression of the immune system [15][16][17].…”
Section: Classifications Of Dmts For Use In Rrmsmentioning
confidence: 99%
“…These DMTs can also be classified broadly according to their pharmacological mechanisms of action. For example, dimethyl fumarate, teriflunomide, fingolimod, natalizumab, and the anti-CD20 agents ocrelizumab and ofatumumab [14] (the latter is newly approved for the management of RRMS in the USA) are continuously administered immunosuppressants. Interferons and glatiramer acetate are administered continuously and act via complex mechanisms that do not require a generalised suppression of the immune system [15][16][17].…”
Section: Classifications Of Dmts For Use In Rrmsmentioning
confidence: 99%
“…There are three major mAbs targeting CD20+ B-cells, rituximab, ocrelizumab, and ofatumumab. The mechanisms of apoptotic B-cell depletion include antibody-dependent cell-mediated phagocytosis, antibody-dependent cellular cytotoxicity (ADCC), and complement-dependent cytotoxicity (CDC) ( 28 , 31 ). Recent studies have shown also a depleting action on CD20+ T cells, which are shown to be present in MS patients, suggesting an alternative contributing mechanism ( 38 ).…”
Section: Introductionmentioning
confidence: 99%
“…Common adverse reactions associated with ocrelizumab are mostly related to increased infections including skin infections and upper respiratory infections; however, malignancy particularly of the breast has been reported earlier in the clinical trials. 16 - 18 …”
Section: Introductionmentioning
confidence: 99%